Vitamin D and Acute Diarrhea in Children: A Meta-Analysis - Manoppo, Jeanette I. Christiene; Takumansang, Raynald O.; Halim, Rifrita Fransisca (Green Publisher Indonesia, 2023)
Diarrhea remains a significant health concern worldwide, particularly in developing countries, contributing to 10% of deaths in children under 5 years. Bacterial infections, notably Shigella and Enteropathogenic Escherichia coli (EPEC), are prevalent causes. This study explores the association between vitamin D3 levels and acute diarrhea in children through a systematic literature review and meta-analysis. Ten studies, including case-control, cross-sectional, and cohort designs, were analyzed. The meta-analysis revealed a significant relationship between vitamin D3 deficiency and acute diarrhea, indicating a higher risk in children with lower vitamin D3 levels. While conflicting findings exist, this study provides valuable insights into the potential role of vitamin D3 in mitigating the risk of acute diarrhea in children.